If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + -13) = (2x + 1) + (3x + 2) Reorder the terms: (-13 + 7x) = (2x + 1) + (3x + 2) Remove parenthesis around (-13 + 7x) -13 + 7x = (2x + 1) + (3x + 2) Reorder the terms: -13 + 7x = (1 + 2x) + (3x + 2) Remove parenthesis around (1 + 2x) -13 + 7x = 1 + 2x + (3x + 2) Reorder the terms: -13 + 7x = 1 + 2x + (2 + 3x) Remove parenthesis around (2 + 3x) -13 + 7x = 1 + 2x + 2 + 3x Reorder the terms: -13 + 7x = 1 + 2 + 2x + 3x Combine like terms: 1 + 2 = 3 -13 + 7x = 3 + 2x + 3x Combine like terms: 2x + 3x = 5x -13 + 7x = 3 + 5x Solving -13 + 7x = 3 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -13 + 7x + -5x = 3 + 5x + -5x Combine like terms: 7x + -5x = 2x -13 + 2x = 3 + 5x + -5x Combine like terms: 5x + -5x = 0 -13 + 2x = 3 + 0 -13 + 2x = 3 Add '13' to each side of the equation. -13 + 13 + 2x = 3 + 13 Combine like terms: -13 + 13 = 0 0 + 2x = 3 + 13 2x = 3 + 13 Combine like terms: 3 + 13 = 16 2x = 16 Divide each side by '2'. x = 8 Simplifying x = 8
| 12x^2-47x-40=0 | | 22x-32=56 | | 2(x-1)-6=10(1-x)+6 | | y+0.1=-22.4 | | -5p+10+2p=-5 | | -1.5x^2-2.5x=0 | | -1.5x-2.5x=0 | | (2x+5)=(4x-35) | | x^2+48x+47=0 | | 6+3x+6x=-3+x+1+7x | | 8-2v-2=3-3v | | 7x-8-3x=24 | | 1+9=9+1 | | z+18=30 | | 10x+5Y=3621 | | 122-6x=21x+23 | | 122-6x=221x+23 | | 10-7x=30-14x | | -65-8x=8x+15 | | x^3-2x^2-3x=0 | | -42-3x=6-9x | | 9x^2+24x=-16 | | 3(2x+4)+8=50 | | ax=bx+c | | 4x^2=-12x+10 | | 10a-5b=12 | | x(4x^2-20x+24)=0 | | 8+3x=23 | | 100y+30=120y+90 | | x-6=x+21 | | x-6=x-21 | | 3(3-4d)=57 |